The effect of programmed relaxation exercises on the shooting of basketball freethrows - Iselin, Walter C. Jr. (My University, 1979)
The present investigation examined the effectiveness of programmed relaxation exercises in conjunction with mental practice on the performance of shooting basketball free-throws. The Ss were (N=24) female intercollegiate basketball players from the University of Wisconsin- La Crosse. The investigation utilized audio tapes for the administration of 2 parts of the study, the mental practice section and the programmed relaxation exercises. Ss in the experimental group participated in 10 sessions of relaxation training combined with mental and physical practice.Ss control group experienced 10 sessions with only mental and physical practice.
Keywords: Relaxation; Motor ability; Basketball